The Fifth Generation Regional Climate Modeling System, RegCM5: Description and Illustrative Examples at Parameterized Convection and Convection‐Permitting Resolutions. Issue 6 (27th March 2023) - Giorgi, Filippo; Coppola, Erika; Giuliani, Graziano; Ciarlo`, James M.; Pichelli, Emanuela; Nogherotto, Rita; Raffaele, Francesca; Malguzzi, Piero; Davolio, Silvio; Stocchi, Paolo; Drofa, Oxana
Abstract: We introduce the latest version of the RegCM regional climate modeling system, RegCM5. Compared to the previous model version (RegCM4) the main new development is the inclusion of the non‐hydrostatic dynamical core from the weather prediction model MOLOCH, which is more accurate and much more computationally stable and efficient than the previous one. In particular, the new dynamical core is best designed for use at convection‐permitting resolutions of a few km. Several physics schemes and coupled model components have also been upgraded compared to the previous version of the model. A set of test simulations for present day climate conditions at parameterized convection and convection permitting resolutions over different European domains is presented for illustrative purposes. Overall, for these simulations RegCM5 exhibits a better performance than RegCM4 for the majority of statistics analyzed, especially at convection‐permitting resolutions. However, this performance depends on the physics schemes used, and further optimization work is under way to fully test the model in different climate settings and reduce current biases. RegCM5 is a freely available, computationally efficient, flexible, and portable Regional Earth System model designed for community use, so that prospective model users are welcome to access its code and use it for different applications. Plain Language Summary: We introduce the latest version of the RegCM regional climate modeling system, RegCM5, in which the main new development, in addition to some physics upgrades, is the inclusion of the non‐hydrostatic dynamical core from the weather prediction model MOLOCH. This makes the model more accurate and much more computationally efficient than the previous version, especially at convection‐permitting resolutions of a few km. A set of test simulations for present day climate conditions at parameterized convection and convection permitting resolutions over different European domains is presented for illustrative purposes. Overall, these simulations show that RegCM5 mostly exhibits a better performance than RegCM4 for most statistics analyzed, especially at convection‐permitting resolutions, although this performance depends on the physics schemes used. Further optimization work is under way to fully test the model in different climate settings and reduce current biases. RegCM5 is a freely available, computationally efficient, flexible, and portable Regional Earth System model designed for community use, so that prospective model users are welcome to access its code and use it for different applications. Key Points: The fifth version of the regional climate modeling system RegCM, has been developed and released Illustrative experiments show that the model overall performs better and is much more computationally efficient than the previous version The model is a community resource so that prospective users are encouraged to access it and use it